Outcomes of Composite Grafts for Pediatric Fingertip Amputations: A Systematic Review - Jester, Noemi; Han, Seunghee; Singh, Manwi; Rao, Avula Aishwarya; Sokhal, Balamrit; Ma, Yangmyung; Jester, Andrea (Indian Journal of Plastic Surgery, 2023)
Introduction The aim of this study was to explore the outcomes of composite grafts in fingertip amputations in children as well as the contributing factors that may affect outcomes.Methods Literature search was conducted across six databases in March 2022 to select studies on the use of composite grafts on fingertip amputations in the pediatric population.Results Twelve articles with 735 composite grafts were identified for review. Most fingertip injuries occurred in the less than 5-year age group and were due to crush type injuries. In studies that reported “complete” graft take as a separate outcome measure, 17.3% of fingertips with this result were observed. In the studies that reported “complete” and “partial” graft take together as an outcome measure, 81.6% of fingertips achieved this outcome. A lower proportion of failed graft take was observed in more distal fingertip amputations. Infection (3.8%) and nail abnormalities (3.4%) were the most common complications following composite grafting.Conclusion Composite grafting can be considered as a useful method of treatment in this population. Clinicians should be aware of the potential complications following this method of treatment such as infection and nail abnormalities. More proximal fingertip amputations may warrant other surgical interventions (beyond Level II on the modified Ishikawa/Ishikawa classification). Significant heterogeneity was observed within the studies, mainly due to lack of standardization in assessment and reporting of outcomes.
Keywords: amputations; composite graft; fingertip; pediatric